PERAN ORIENTASI PASAR DAN ORIENTASI KEWIRAUSHAAN TERHADAP INOVASI PRODUK DAN KINERJA PEMASARAN PADA UMKM TANGGUI DI LINGKUNGAN LAHAN BASAH (Studi Pada Pengrajin Tanggui Di Alalak) - RR. Yulianti Prihatiningrum; Gusti Rina Fariany (JWM (JURNAL WAWASAN MANAJEMEN), 2020)
The main purpose of this study was to examine the effect of market orientation and entrepreneurship orientation on product innovation and marketing performance. The respondents of this research were tanggui craftsman at Alalak, in North Banjarmasin, South Borneo, Indonesia which consists of 70 people. The Method sampling used was convenience sampling, and the data collection technique used a survey with a questionnaire tool.The verification analysis used Structural Equation Modeling with Partial Least Square (SEM-PLS) approach. The research results showed that market orientation and entrepreneurship orientation have a positive and significant impact on product innovation (H1 and H2 were supported), also marketing orientation was significantly influenced by product innovation (H3 was supported).